The Effect of Contextual Learning Model on Students' Learning Outcomes in Science Subjects In Grade III - Siahaan, Bethesda Angela; Panjaitan, Muktar B; Simamora, Aprido (Jurnal Ilmu Sosial dan Humaniora, 2026)
This study aims to determine the effect of using the contextual learning model on the learning outcomes of Natural and Social Sciences (IPAS) students in Grade III at UPTD SD Negeri 122399 Jl. Mawar Pematangsiantar. The research instrument consisted of cognitive test items that had undergone validity and reliability tests, resulting in 20 valid and reliable items with a high reliability coefficient of 0.885. These test items demonstrated good discriminative power and an appropriate difficulty level for third-grade elementary students. Data were collected through pretests and posttests administered before and after the treatment using the contextual learning model. The pretest results showed an average student score of 44.4, with 23 students not meeting the Learning Achievement Criteria (KKTP), while the posttest showed a significant increase with an average score of 79.6 and 23 students declared passing. Data analysis using the Shapiro-Wilk normality test revealed a normal distribution, and hypothesis testing yielded a significance value of 0.00 (p < 0.05) with tcount > ttable. Therefore, it can be concluded that there is a significant effect of using the contextual learning model on IPAS learning outcomes. Observational results support these findings by indicating increased student engagement and interest during the learning process. Overall, this study concludes that the contextual learning model positively contributes to the improvement of IPAS learning outcomes for Grade III students at the schoo